THE QUALITY OF DIGITAL SPATIAL DATA AS A DETERMINING COMPOSITION OF INFORMATION SUPPORT OF MODERN GENERAL-GEOGRAPHICAL MAPS - Бондаренко, Е.; Писаренко, Р. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
The article deals with the questions of the quality of digital spatial data in the algorithm for creating general-geographic maps. The place of information of this property based on the formulated methodological principles (heredity, continuity, consistency, representativeness, scale, efficiency) ) is substantiated. The author reveals the essence of the basic elements of information on the quality of digital spatial data. The principles of its provision with respect to errors (prevention, finding, removal, tolerance) are defined. The sequences of determining the qualities of digital spatial data (on the example of general-geographic maps of different base scales) are specified. Keywords: quality of digital spatial data, information support, algorithm for creating general-geographic maps, basic scale.